Precoding Design for Multi-Group MIMO-NOMA Scheme With SIC Residual Analysis - Zhang, Rongbin; Liu, Huajiao; Leung, Shu-Hung; Zhang, Yue; Tang, Weijun; Wang, Hong; Luo, Zhen; Roy, Sumit (IEEE transactions on vehicular technology, 2023)
This paper presents a precoder design for multiple-input multiple-output (MIMO) uplink communications with a multi-group non-orthogonal multiple access (NOMA) scheme. In this scheme, QR-decomposition-based detection is used to decode user signals of each group under imperfect successive interference cancellation (SIC). In the uplink, transmitted signals are encoded with the constellation of a symmetric quadrature amplitude modulation (QAM), and SIC residual errors are generated from symbol demodulation. The statistics of the SIC errors are derived, with which expressions of approximate SIC-residual-power coefficient and signal-to-interference-plus-noise ratio (SINR) are developed. Consequently, the effect of the SIC errors can be explicitly addressed in the precoder design for minimizing the total transmit power subject to users' symbol error probability (SEP) constraints. A suboptimal design algorithm with efficient "logarithmic" golden-section search is developed. Simulation results show the effectiveness of the design criterion and algorithm, and validate the detection error analysis. Unlike the conventional fractional-SIC-error model that suffers from underestimation/overestimation of SIC errors and infeasibility, our SIC error model can provide accurate effect of the SIC errors in the SINR analysis and enable the proposed method to give design solutions to satisfy the SEP constraints.